Raising Anemia Awareness in Pregnant Women through Visual Education and Interactive Dialogue in Petaling Banjar Village, Bangka Regency - Yanti, Eka Safitri (LP2M INSURI Ponorogo, 2025)
Anemia during pregnancy remains a major public health issue in Indonesia, particularly in rural areas where maternal knowledge and adherence to iron supplementation are still limited. In Petaling Banjar Village, preliminary observations revealed persistent cases of anemia and limited access to structured nutrition education for pregnant women—this community engagement aimed to improve maternal understanding of anemia through audiovisual education and interactive dialogue. The program was conducted in Petaling Banjar Village using an integrated approach that comprised video presentations, booklet distribution, and open discussions, involving 17 pregnant women who actively participated in sharing their experiences and asking questions. Evaluation was performed by comparing pretest and posttest knowledge scores using descriptive analysis and a paired t-test. The results showed an increase in the average score from 87.1 to 96.5, with a p-value of 0.000 indicating a significant difference. Media-based and participatory education proved effective in enhancing maternal knowledge and raising awareness of anemia prevention. These findings underscore the importance of context-based and participatory community education in supporting sustainable maternal and child health outcomes.